PENERAPAN SUPERVISI AKADEMIK DI PAUD - Lutfhi Assagaf (LP2M STIT Al-Hikmah Way Kanan, 2020)
Abstract This study applies the academic supervision program in PAUD PGRI Bumi Agung, using an evaluation model of Context, Input, Process, Product (CIPP). The results of this study are expected to provide input to decision makers for further programs. The descriptive-qualitative research respondents included the principal, six teachers, and school managerial staff. Data collection is done through interviews, observations and document studies. Data source triangulation and data validation methods are then analyzed through data condensation, data display, conclusion drawing and verification. The findings show a context evaluation reveals the need for supervisory academics based on conditions and the need to improve teacher quality. Evaluation inputs describe well-planned programs - using different techniques, involving teacher readiness, supported by budget and available infrastructure. The evaluation process reports on the implementation of the planned technique, with some adjustments based on the ongoing conditions, supported by teacher readiness and participation and how they handle obstacles. The product evaluation found that academic supervision programs have a positive impact and achieve planned goals. There was also a positive response from the teacher and several follow-up plans. Finally, this study provides recommendations for improving local supervision programs, inputs to management schools, and ideas for future research. Keywords: supervision, academic